Atrial Fibrillation and Heart Failure: Convergence of Two Epidemics - Roy, Denis; Doshi, Rahul N.; Hsu, Li-Fern; Friedman, Paul A. (MD Conference Express, 2006)
Atrial arrhythmias are common in patients with heart failure (HF), regardless of underlying etiology. Indeed, atrial fibrillation (AF) and HF coincide (AF/HF) in 10–15% of patients in class II-III HF, and each can exacerbate the other. “Neither AF or HF can be properly managed independently of each other,” said Denis Roy, MD, Professor of Medicine, University of Montreal.